2004
DOI: 10.1016/j.molcel.2004.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Skp, a Prefoldin-like Chaperone that Protects Soluble and Membrane Proteins from Aggregation

Abstract: The Seventeen Kilodalton Protein (Skp) is a trimeric periplasmic chaperone that assists outer membrane proteins in their folding and insertion into membranes. Here we report the crystal structure of Skp from E. coli. The structure of the Skp trimer resembles a jellyfish with alpha-helical tentacles protruding from a beta barrel body defining a central cavity. The architecture of Skp is unexpectedly similar to that of Prefoldin/GimC, a cytosolic chaperone present in eukaria and archea, that binds unfolded subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
218
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(229 citation statements)
references
References 37 publications
9
218
0
2
Order By: Relevance
“…1A) (8,9). The Skp structure was unexpectedly similar to that of prefoldin, a cytosolic molecular chaperone present in archea and eukarya (8)(9)(10). Although Skp is a trimer (8,9,11) and prefoldin is a hexamer (12,13), both proteins share jellyfish architectures with a central cavity ( Fig.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…1A) (8,9). The Skp structure was unexpectedly similar to that of prefoldin, a cytosolic molecular chaperone present in archea and eukarya (8)(9)(10). Although Skp is a trimer (8,9,11) and prefoldin is a hexamer (12,13), both proteins share jellyfish architectures with a central cavity ( Fig.…”
mentioning
confidence: 86%
“…Previous studies have shown that Skp can prevent the aggregation of model proteins like lysozyme (8). We next wanted to test Skp function with a true OMP substrate.…”
Section: Skp Prevents the Aggregation Of Ompa By Forming A Stable Commentioning
confidence: 99%
See 2 more Smart Citations
“…Crystal structures are also available for the cytosolic chaperone prefoldin and the bacterial periplasmic chaperone Skp, and these reveal a strikingly similar overall architecture given that the proteins have no evolutionary relationship (32)(33)(34)(35). Prefoldin is a 90 kDa complex of two a and four b subunits present in the cytosol of eukaryotes and archea (36, 37) (Fig.…”
Section: Structure Of the Small Tim Chaperonesmentioning
confidence: 99%